Crystal structure of bis(μ2-pyrrolidine-1-carbodithioato-κ3 S,S′:S;κ3S:S:S′)-bis(tricyclohexylphosphane-P)-di-copper(I), C46H82Cu2N2P2S4 - Tan, Yi Jiun *; Yeo, Chien Ing *; Halcovitch, Nathan R.; Tiekink, Edward R. T. * (De Gruyter Open Access, 2018)
C46H82Cu2N2P2S4, triclinic, P¯1 (no. 2), a=11.6189(2) Å, b=12.2846(2) Å, c=18.1744(2) Å, α=97.3210(10)°, β=106.3080(10)°, γ=99.312(2)°, V =2415.65(7) Å3, Z =2, Rgt(F)=0.025, wRref(F2)=0.066, T =100(2) K.